A Study on Green Synthesis of Nano Cu Compounds (Malachite and Rouaite), Using Moringa oleifera Leaf Extract and their Photocatalytic, Antifungal, Anti-Inflammatory, and Antioxidant Properties - S. Darani; N. Nivedha Devi; R. Rajakumari (New Innovations in Chemistry and Biochemistry Vol. 2, 2021)
Nano copper compounds (Malachite and Rouaite) were synthesized using Moringa oleifera leaf extract as the reducing agents and characterized by X-ray diffraction and Scanning electron microscopic analysis, respectively, for structure and morphology. The UV-vis absorption analysis of Malachite exhibits multiple peaks, and the energy bandgap obtained from the Taue plot was 5.32 eV for malachite and 3.7 eV for Rouaite. The photoluminescence spectra of Malachite and Rouaite show broadband emission in the green region of the visible spectrum. The photocatalytic activity of Malachite and Rouaite was examined with the natural dye of beetroot (Beta vulgaris) extract and observed that the absorption peak intensity of the dye decreases as the time of exposure to sunlight increases, indicating the degrading effect of the synthesized samples. The antifungal activity of Malachite and Rouaite with Candida albicans by agar disc diffusion method showed that Rouaite has more enhanced antifungal activity than Malachite. Thus, it is suggested that the green synthesized Rouaite and Malachite may be used in medicine for their antifungal and anti-inflammatory activities.